Implementing Quick Response Manufacturing to Improve Delivery Performance in an ETO Company - Cheng Siong, Bong; Kuan Eng, Chong (International Journal of Engineering and Technology, 2018)
As the pressure is increasing to compete with others to get customer orders in the global market, companies are struggling to build up competitive advantages that are hard to imitate. The trend shows more and more customers demand faster product delivery in the last decade. The Quick Response Manufacturing (QRM) approach provides significant benefits to engineer-to-order (ETO) companies through its focus on lead time reduction. A precision parts manufacturer was selected as case study to what extent QRM is a suitable solution to improve the delivery performance. This paper describes the implementation of the QRM concepts and illustrates how they were deciphered into practices that streamline the process across the organization. The study measures the effectiveness of the QRM framework through its ability to achieve better performance through concurrently reducing manufacturing critical-path time, lowering capacity utilization level and increasing throughput.Â Â